Demography, commonly recorded disorders and mortality in chelonia under UK primary veterinary care: A VetCompass study - Jessica May Hornby; Joanna Hedley; Dave C. Brodbelt; David B. Church; Dan G. O’Neill (PLoS ONE, 2025)
Little information has been published on the recorded disorders of pet chelonia. This cohort study aimed to report on demography, commonly recorded disorders and mortality recorded in chelonia under UK primary veterinary care in 2019. Electronic health records on a random sample of chelonia in VetCompass during 2019 were reviewed to extract species, recorded disorder and mortality data. Of 2,040 chelonia reviewed, 1,923 (94.26%) were recorded as tortoises, 74 (3.63%) terrapins and 43 (2.11%) turtles. Of the 811 (42.17%) tortoises with species information recorded, the most common species were Hermann’s tortoises (Testudo hermanni) (311, 38.35%), Horsfield’s tortoises (Testudo horsfieldii) (259, 31.94%) and Mediterranean spur-thighed tortoises (154, 18.99%). The most commonly recorded disorders were beak abnormalities (16.72%), overgrown nails (11.47%) and shell abnormalities (9.80%). The most common recorded causes of death were “disorder undiagnosed” (44.55%), dog bite (5.45%) and anorexia (3.96%). Of 178 deaths with age recorded, the median age at death was 7.32 years (IQR 2.50-15.14). Short temporal windows within the clinical records and often limited clinical workups were a frequent limitation to the precision of the recorded disorder terms. This is the largest study of chelonia to date. It has highlighted the most commonly recorded disorders of chelonia of which many are often linked to husbandry.